2014
DOI: 10.3389/fpsyt.2014.00083
|View full text |Cite
|
Sign up to set email alerts
|

Stress Modulates Illness-Course of Substance Use Disorders: A Translational Review

Abstract: Childhood trauma and post-childhood chronic/repeated stress could increase the risk of a substance use disorder by affecting five stages of addiction illness-course: (a) initial experimentation with substances; (b) shifting from experimental to regular use; (c) escalation from regular use to abuse or dependence; (d) motivation to quit; and (e) risk of (re-)lapse. We reviewed the human literature on relationships between stress and addiction illness-course. We explored per illness-course stage: (i) whether chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 262 publications
(370 reference statements)
5
76
0
1
Order By: Relevance
“…Moreover, AD patients with CM (C+ A+) showed the highest ratings of distress during or after the TSST whereas AD patients without CM (C−A+) showed the lowest ratings. This result seems to support the findings from prior studies that linked higher stress vulnerability to a higher risk of relapse (Lijffijt et al 2014). Significant differences could also be found with regard to the mood ratings with C −A+ participants showing the highest values on the mood scale during the entire course of the investigation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, AD patients with CM (C+ A+) showed the highest ratings of distress during or after the TSST whereas AD patients without CM (C−A+) showed the lowest ratings. This result seems to support the findings from prior studies that linked higher stress vulnerability to a higher risk of relapse (Lijffijt et al 2014). Significant differences could also be found with regard to the mood ratings with C −A+ participants showing the highest values on the mood scale during the entire course of the investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Childhood maltreatment (CM) presents a risk factor for alcohol dependence (AD) and has been linked to a more severe clinical profile and a higher risk for relapse (Keyes et al 2011;Lijffijt et al 2014). One potential factor that has been discussed to moderate the interaction between CM and AD is an altered functioning of the neurobiological stress systems (Keyes et al 2011;Lijffijt et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was necessary due to the restricted sample size. However, both incidence and recurrence of SUDs could be equally related to stressful experiences (Lijffijt et al, 2014;Sinha, 2008), wherefore this strategy seemed appropriate for the purpose of this study. Individuals that already met the criteria for a 12-month SUD diagnosis at Time 1 were excluded from the respective analysis ( Fig.…”
Section: Onset Of Substance Use Disorders (Suds)mentioning
confidence: 97%
“…On a behavioral level, there is some empirical support for the self-medication hypothesis suggesting that individuals use substances to cope with adverse emotional states and psychological symptoms that occur in reaction to SE (Garland, Pettus-Davis, & Howard, 2013;Khantzian, 1997;Magid et al, 2009). It has also been suggested that the link between SE and SUD risk can partially be explained by the effects of SE on individual trait factors such as stress reactivity and behavioral control (Lijffijt, Hu, & Swann, 2014). Addictive Behaviors 43 (2015) [89][90][91][92][93][94][95][96] Importantly, despite noteworthy evidence for a relationship between SE and subsequent SUD, several studies do not find an association between SE and SUD risk Keyes, Hatzenbuehler, Grant, & Hasin, 2012;North et al, 2005;Vlahov et al, 2006).…”
Section: Introductionmentioning
confidence: 99%